Design and Implementation Gaseous Detector of Pollutants in Operating Theaters with an Early Warning System - Razzaq, Muntadhar Wahab; jameel, Taha Raad; Ahmed, Muhammad Alaa (American Journal of Botany and Bioengineering, 2025)
Operating theaters are core across the healthcare sector, playing vital roles in resolving health issues or addressing diseases through surgery or other invasive therapeutic approaches. Airborne environmental pollutants, including anesthesia gases, explosive substances, and airborne bacteria, put surgical patients and healthcare providers at risk. Gaseous pollutant detector solutions offer substantial prospective support for healthcare providers from a social perspective by broadening the monitored gaseous pollutant diversity. Within operating theaters, gaseous pollutant detector systems require a unique kind of engineered structure compared to other gassier environments. A gaseous detector system for pollutants in operating theaters with an early warning capability was designed and implemented. Monitoring of semivolatile organic compounds (SVOCs) and the pre-anesthetic gaseous pollutant is supported by this system to assist healthcare providers in selecting and verifying the operation of Gaseous Filtered Air (GFA) facilities before surgical procedures and after the induction of anesthesia.